Pengecualian Prsidential Threshold terhadap Partai Politik Baru Peserta Pemilihan Umum - Torik Abdul Aziz Wibowo (Fakultas Hukum Universitas Islam Indonesia, 2023)
The Presidential Threshold setting provides a separate previllage for parliamentary Political Parties to nominate a Pair of. Meanwhile, political parties that have just become participants in the general election contestation cannot nominate their presidential and vice-presidential candidates in that election. Meanwhile, the Constitutional Court has consistently stated that the Presidential Threshold is an open legal policy 27 times. This makes the function of political recruitment by new political parties impossible. Kebangkitan Nasional Party (PKN) proposed testing the Presidential Threshold at MK which in the petite of this propose request that the Constitutional Court decide on the application of the presidential threshold to exclude new political parties from participating in the election. So what are the problems with applying the presidential threshold in Indonesian elections? as well as, what is the relevance of implementing the presidential threshold exception for new political parties participating in the election? This paper was prepared based on legal research with a juridical-normative approach using primary legal sources as the main research material. The results of this study conclude first, setting the presidential threshold creates anomalies and discrimination against political parties that have just become election participants. Second, the relevance of the presidential threshold exception is as an antithesis to the symptoms of cartelization that occurred in old political parties Presidential Candidates and Vice Presidential Candidates.